2014
DOI: 10.1111/joor.12162
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oral appliances that advanced the mandible forward and limited mouth opening in patients with obstructive sleep apnea: A systematic review and meta‐analysis of randomised controlled trials

Abstract: Oral appliances (OAs) have demonstrated efficacy in treating obstructive sleep apnea (OSA), but many different OA devices are available. The Japanese Academy of Dental Sleep Medicine supported the use of OAs that advanced the mandible forward and limited mouth opening and suggested an evaluation of their effects in comparison with untreated or CPAP. A systematic search was undertaken in 16 April 2012. The outcome measures of interest were as follows: Apnea Hypopnea Index (AHI), lowest SpO2 , arousal index, Epw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 20 publications
4
36
0
1
Order By: Relevance
“…45 Do podobnych wniosków doszli Okuno i wsp. 46 Smith i Stradling przedstawiają natomiast obie metody jako rów-nie skuteczne w leczeniu OBS. 47 Badanie ankietowe McGowna i wsp.…”
Section: T H I S C O P Y I S F O R P E R S O N a L U S E O N L Y -D Iunclassified
“…45 Do podobnych wniosków doszli Okuno i wsp. 46 Smith i Stradling przedstawiają natomiast obie metody jako rów-nie skuteczne w leczeniu OBS. 47 Badanie ankietowe McGowna i wsp.…”
Section: T H I S C O P Y I S F O R P E R S O N a L U S E O N L Y -D Iunclassified
“…The six reviews 50,52,55,56,59,60 that were identified as having high quality (low risk of bias) found superior efficacy of OAs over controls/placebo/no treatment. These reviews supported a reduction in apnea-hypopnea index (AHI), minimum oxygen saturation level, blood pressure, and arousal index with OAs, in addition to improvement in health-related quality of life.…”
Section: Adult Sdbmentioning
confidence: 99%
“…57 In that review, 57 randomized trials with both parallel and crossover designs were combined in the MA without justification. Only five reviews (38.5%) either assessed publication bias using funnel plots 55,[58][59][60] or described reasons for not investigating it. 56 Five of the 11 MAs 51,56,58-60 conducted sensitivity analyses to assess the robustness of the results.…”
Section: Adult Sdbmentioning
confidence: 99%
See 1 more Smart Citation
“…The main function of MAD is to protrude the mandible forward, causing the airway to remain open during sleep [9]. MAD therapy is also an alternative when patients reject CPAP or when CPAP is not tolerated for various reasons [12]; however, the effect is less powerful than that achieved with CPAP [13].…”
Section: Introductionmentioning
confidence: 99%